Complete mitochondrial genome of a rare diatom (Bacillariophyta) Proschkinia and its phylogenetic and taxonomic implications. Issue 1 (2nd January 2019) - Gastineau, Romain; Kim, So-Yeon; Lemieux, Claude; Turmel, Monique; Witkowski, Andrzej; Park, Jong-Gyu; Kim, Byoung-Seok; Mann, David G.; Theriot, Edward C.
Abstract: We obtained the complete mitogenome of Proschkinia sp. strain SZCZR1824, a strain belonging to a poorly known diatom genus with no previous molecular data. This genome is 48, 863 bp long, with two group I introns in rnl and three group II introns in cox 1. Using mitogenomic data, Proschkinia sp. was recovered with Fistulifera solaris, far distant from Navicula and Nitzschia, two genera with which Proschkinia has sometimes been associated based on morphology.